Challenging factors influencing university students' intention and experience of online learning: an analysis using Berge model - Ilias A.; Baidi N.; Ghani E.K.; Razali F.M. (Inderscience Publishers, 2024)
This study examined the Malaysian university students' experience of online learning (OL) usage challenges during the COVID-19 pandemic using Berge model among gender, experience, and intention. It examined the association between experience of online learning usage and intention to use online learning. This study surveyed 436 students via an electronic questionnaire. The view on technical skills and learner motivation are different among genders. Furthermore, students with experience and those with no experience of online learning have different views on academic skills. Students that have an intention and those with no intention to use OL have different views on social interactions, academic skills, time and support for studies, cost and access and technical problems. The experience of OL usage has shown an association with intention to use OL. This study contributes to the implementation of OL that involves instructors and students and the motivation to use OL with instructors' preparedness, teaching content, time, and voice usage. 2023 Inderscience Enterprises Ltd.